2012
DOI: 10.1590/s0103-90162012000100008
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in vegetables and potential risk for human health

Abstract: Ingestion of vegetables containing heavy metals is one of the main ways in which these elements enter the human body. Once entered, heavy metals are deposited in bone and fat tissues, overlapping noble minerals. Slowly released into the body, heavy metals can cause an array of diseases. This study aimed to investigate the concentrations of cadmium, nickel, lead, cobalt and chromium in the most frequently consumed foodstuff in the São Paulo State, Brazil and to compare the heavy metal contents with the permissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
158
10
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(186 citation statements)
references
References 16 publications
13
158
10
5
Order By: Relevance
“…Similarly, these levels are higher than the results found on tomatoes in other countries on tomatoes: Karavoltsos et al [33] in Greece reported a total Cd content of 0.0188 ppm, Mohamed et al [34] in Egypt reported 0.01 ppm for total Cd and 0.26 ppm for total Pb. Likewise Guerra et al [35] in São Paulo in Brazil found a total Cd content of 0.02 to 0.04 ppm. Another study reported by Radwan and Salama [36] in Egypt shown a value of 0.01 ppm for total Pb.…”
Section: Resultsmentioning
confidence: 84%
“…Similarly, these levels are higher than the results found on tomatoes in other countries on tomatoes: Karavoltsos et al [33] in Greece reported a total Cd content of 0.0188 ppm, Mohamed et al [34] in Egypt reported 0.01 ppm for total Cd and 0.26 ppm for total Pb. Likewise Guerra et al [35] in São Paulo in Brazil found a total Cd content of 0.02 to 0.04 ppm. Another study reported by Radwan and Salama [36] in Egypt shown a value of 0.01 ppm for total Pb.…”
Section: Resultsmentioning
confidence: 84%
“…Rape and potatoes sold by supermarkets, had high concentrations of lead which was above the permissible limit and therefore regarded unsafe for human consumption. Other studies (Guerra et al 2012;Harmanescu et al 2011;Abbas et al 2010;Yang et al 2011) obtained ranges; 470 -1660 µg/Kg, 4.5 -21.8 mg/Kg, 18 -150 µg/Kg and 6 -16 mg/Kg in Brazil, Nigeria, Pakistan and China respectively.…”
Section: Leadmentioning
confidence: 88%
“…Cadmium is a hazardous element which has been associated with various complications like bone de-calcification, renal, membrane and DNA damages (Guerra et al 2012). Research studies have found that vegetables contribute about 70% cadmium intake by humans, varying according to the level of consumption (Wagner, 1993in Rivera-becerril et al 2002.…”
Section: Cadmiummentioning
confidence: 99%
“…Researchers have demonstrated its toxic effects on plants (Aery & Rana, 2003;Hasan et al, 2007). In a recent study, Guerra et al (2012) found that Cd did not exceed the critical limit (1.0 mg kg -1 , fresh weight) for human consumption in a set of vegetables samples collected at a distribution center in the city of São Paulo, Brazil.…”
Section: Introductionmentioning
confidence: 98%